Book Review: Cross, M. and Ndofirepi, A. (Eds.).2017.Knowledge and change in African universities Volume 1 –Current Debates, and Re–imagining the terrain Volume 2.Rotterdam: Sense - Trahar, Sheila (Critical Studies in Teaching and Learning, 2023)
Some years ago, I was involved in a project with three universities in sub-Saharan Africa and subsequently, with another one in Cameroon. Since 2015, I have been engaged in research projects in South Africa and have been reading voraciously to further understand the complexities of higher education in the South African context, as well as the other sub-Saharan countries with whom I previously worked.